Dissecting the contribution of innate and antigen-specific pathways to the breach of self-tolerance observed in a murine model of arthritis. Issue 6 (17th July 2008) - Nickdel, M B; Conigliaro, P; Valesini, G; Hutchison, S; Benson, R; Bundick, R V; Leishman, A J; McInnes, I B; Brewer, J M; Garside, P
Abstract : Background: The relative roles of innate immunity and antigen-specific T cells in rheumatoid arthritis remain controversial. Previous studies demonstrated that T-helper type 1 cells of irrelevant antigen specificity (ovalbumin) induced a transient arthritis in BALB/c mice, which recapitulates many of the pre-articular and articular features of human disease and is associated with the emergence of autoreactive T and B-cell responses to joint-specific antigens. However, the mechanisms underlying this phenomenon were unclear. Objectives: The aim of this study was to dissect the relative contribution of innate and heterologous antigen-specific pathways to the breach of self-tolerance and pathology observed in this model and how this may result from modified T and B-cell interactions. Methods: To address this issue, experimental arthritis was elicited either by a non-specific inflammatory stimulus alone, by activation of T cells of an irrelevant specificity or a combination of both. Results: The non-specific inflammatory response generated by lipopolysaccharide led to articular inflammation and cartilage erosion, but did not break tolerance to joint-specific antigens. In contrast, local activation of T cells of an irrelevant specificity produced a similar pathological picture but, in addition, induced T-cell responses to unrelated joint-specific antigens with associated activation of autoreactive B cells. These effects could be further potentiated by the addition of lipopolysaccharide. Conclusion: These data demonstrate that non-specific inflammation alone is insufficient to breach self-tolerance. In contrast, T cells of an irrelevant specificity, when triggered locally in an antigen-specific manner, can breach self-tolerance leading to arthritis and autoantibody production, which can then be amplified in a non-specific manner.